1992
DOI: 10.1177/030006059202000305
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Gluconate and the Common Cold: A Controlled Clinical Study

Abstract: A report in 1984 on the success of zinc gluconate against common cold symptoms could not be confirmed in three subsequent studies, which are now known to have used formulations that inactivated zinc. A non-chelating formulation including glycine, which releases 93% of contained zinc into saliva, was tested in a randomized, placebo-controlled, double-blind trial in 73 young adults. Efficacy was recorded in symptom diaries using a symptom severity rating. Patients' symptoms first appeared 1.34 days prior to entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 29 publications
(46 reference statements)
2
105
0
1
Order By: Relevance
“…30 Other bias was unclear in three trials. 30,34,35 Sensitivity analysis excluding these trials did not change the results, so the evidence was not downgraded. b Serious inconsistency: Very high statistical heterogeneity (I 2 = 95%).…”
Section: E556mentioning
confidence: 98%
See 3 more Smart Citations
“…30 Other bias was unclear in three trials. 30,34,35 Sensitivity analysis excluding these trials did not change the results, so the evidence was not downgraded. b Serious inconsistency: Very high statistical heterogeneity (I 2 = 95%).…”
Section: E556mentioning
confidence: 98%
“…Zinc may also reduce the severity of cold symptoms by acting as an astringent on the trigeminal nerve. 9,10 A recent meta-analysis of randomized controlled trials concluded that zinc was effective at reducing the duration and severity of common cold symptoms. 11 However, there was considerable heterogeneity reported for the primary outcome (I 2 = 93%), and subgroup analyses to explore betweenstudy variations were not performed.…”
Section: -7mentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc lozenges appeared to have positive effects on adults but negative effects on children in terms of duration and severity of common cold symptoms (Macknin, Piedmonte et al 1998;Marshall 2000). Higher doses were found to have a greater impact in reduction of symptom duration and reduced symptom severity (Godfrey, Conant Sloane et al 1992;Mossad, Macknin et al 1996). Zinc nasal spray appears to reduce the total symptom score but has no effect on the duration of common cold (Belongia, Berg et al 2001).…”
Section: Prevention and Treatment For Respiratory Virusesmentioning
confidence: 99%